Journalists want virtuous physicians? An analysis by the model of Ethic of Virtues, in reference to Beneficence, according to Pellegrino and Thomasma - Ortona, Concília; Fortes, Paulo (Acta Bioethica, 2015)
A search of notes written by Brazilian journalists specialized in Health, representatives of major newspapers and magazines in the country, indicate that the main factor of Humanization of health care is the existence of virtuous physicians. They are capable of providing welfare and put patients’ interests above their own. Therefore, health care based on Beneficence of patients. This draws attention, because it is a country where, in the field of bioethics, the model of Virtues, in the way it is taught by Edmund Pellegrino and David Thomasma, has been little studied. This also shows that autonomous attitudes of patients are poorly valued by respondents, but this may not mean yearning for paternalistic attitudes, but a benevolent attitude, recognizing the vulnerable condition in people who are sick.